(untitled) (Global Journal of Management and Business Research, 2025)
Envisage Infinitive is a futuristic International Business and Global Marketing model that outdates contemporary international business and global marketing models. It overcomes many obstacles, hurdles, and challenges faced by companies from developed countries such as the U.S.A., Canada, France, Germany, Britain, and the rest of Europe, as well as developing countries that are manufacturing giants like India and China. These nations seek to expand internationally and globally but are constrained by stringent import–export and tariff policies, as well as socio-economic conditions shaped by the current global scenario. The model addresses the paradox wherein opportunities for global expansion often coexist with widespread criticism of outsourcing and manufacturing relocation, leading to redundancy and socio-economic disruptions. These challenges have global repercussions, prompting countermeasures and protectionist policies from various countries that restrict foreign products to safeguard domestic production-thereby hampering socio-economic prosperity and shrinking the global market space.